Evaluasi Efisensi Riser Untuk Bentuk Riser Samping yang Berbeda Menggunakan Metode Simulasi Casting - Galuh Bahari; Benidiktus Tulung Prayoga (P3M Politeknik Negeri Cilacap, 2023)
As the solidification reaches the hot spot area, no molten metal remains and shrinkage is formed. To anticipate the shrinkage, a riser is added to the casting system. An optimal riser design would produce free shrinkage components. One of the factors that affect riser efficiency is the riser shape. This study aims to find the most efficient side riser shape by using simulation software. The riser shape of tubes, tubes with a half sphere on top, hemispheres, conical tubes, tubes with an oval cross-section, and cubes are used in this experiment, with the volume of all risers kept constant. The most efficient shape of the riser is the tube. The tube riser produces a larger modulus. The tube riser generated directional solidification. The same pattern can be seen in the niyama criteria and solidification temperature, where the tube riser has a more continuous pattern compared to other riser shapes.